Conventional intensive logging promotes loss of organic carbon from the mineral soil. (13th July 2016) - Dean, Christopher; Kirkpatrick, James B.; Friedland, Andrew J.
Abstract: There are few data, but diametrically opposed opinions, about the impacts of forest logging on soil organic carbon (SOC). Reviews and research articles conclude either that there is no effect, or show contradictory effects. Given that SOC is a substantial store of potential greenhouse gasses and forest logging and harvesting is routine, resolution is important. We review forest logging SOC studies and provide an overarching conceptual explanation for their findings. The literature can be separated into short‐term empirical studies,  longer‐term empirical studies and long‐term modelling. All modelling that includes major aboveground and belowground biomass pools shows a long‐term (i.e. ≥300 years) decrease in SOC when a primary forest is logged and then subjected to harvesting cycles. The empirical longer‐term studies indicate likewise. With successive harvests the net emission accumulates but is only statistically perceptible after centuries. Short‐term SOC flux varies around zero. The long‐term drop in SOC in the mineral soil is driven by the biomass drop from the primary forest level but takes time to adjust to the new temporal average biomass. We show agreement between secondary forest SOC stocks derived purely from biomass information and stocks derived from complex forest harvest modelling. Thus, conclusions that conventional harvests do not deplete SOC in the mineral soil have been a function of their short time frames. Forest managers, climate change modellers and environmental policymakers need to assume a long‐term net transfer of SOC from the mineral soil to the atmosphere when primary forests are logged and then undergo harvest cycles. However, from a greenhouse accounting perspective, forest SOC is not the entire story. Forest wood products that ultimately reach landfill, and some portion of which produces some soil‐like material there rather than in the forest, could possibly help attenuate the forest SOC emission by adding to a carbon pool in landfill.